Sosialisasi Penerapan CHSE Selama Libur Lebaran di Destinasi Wisata Taman Loang Baloq Kota Mataram - Uwi Martayadi; Dyah Indraswati (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
The Community Service Activities (PKM) on the Socialization of CHSE Implementation in Loang Baloq Park have two primary objectives: increasing manager awareness of health protocols during the Eid holiday and maintaining cleanliness, health, safety, and environmental preservation in the park. Through lecture and discussion methods, the PKM project successfully enhances understanding of health protocols among managers and raises their awareness of the importance of these measures in Loang Baloq Park. Moreover, the project aims to protect the health of managers and tourists, instill confidence in visitors, sustain the park's integrity, and create a clean and safe environment for all.